The Law Protection for the Woman Victim of Violence on Traditional Marriage - Wadjo, Hadibah Zachra (SASI, 2022)
Introduction: The law regulation about the elimination of domestic violence has been regulated on dalam Law Number 23 of 2004 about The Elimination of Domestic Violence that, “to prevent, protect the victim, and take action to the domestic violence perpetrator, country, and society must do the prevention, protection, and the perpetrator prosecution that suitable with the Pancasila’s philosophy and the 1945 Constitution of the Republic of Indonesia”.Purposes of the Research: The victim who is bound by marriage that has been done traditionally but not done civilly.Methods of the Research: The research’s method on this writing is using the normative research’s method. A research’s method that been done with researching the library materials towards the regulations and literatures that relate with the problem that be researched. The Data that used is the secondary data with the secondary and tertiary legal materials collection priority. Then the data that be obtained are processed and served descriptively-analysis.Results of the Research: The research’s results shows that the domestic violence that be experienced by the women who her marriage has been done traditionally based on the Law of The Elimination of Domestic Violence can be categorized as the Domestic Violence Criminal Act, but on the handling, the investigator keep to do the things that be mandated by the constitution by giving the victim’s rights and the law protection. The marriage’s status that been done traditionally doesn’t have the fixed legal foundation. But, the country keep guarantee the traditional existence in Indonesia.